(untitled) (Academicia Globe: Inderscience Research, 2024)
This scientific article analyzes the issues of reforming public administration and bodies. In order to improve the efficiency of public administration organizations, foreign experience in this regard has been studied. Based on the study, scientifically based conclusions were drawn.